RECONSTRUCTING AN EFL PRE-SERVICE TEACHER’ IDENTITY: A SELF-NARRATIVE - Abdullah, Achmad Rhazes; Maharsi, Ista (Universitas Putera Batam, 2025)
The experiences of English language education students significantly shape language learning practices and pedagogical approaches globally. Despite the growing interest in these experiences, research on the intersection of identity and language teacher development remains limited, particularly among Indonesian English education students. This study employed James Paul Gee's Identity Theory (2000) to explore the construction and reconstruction of my identity as an English education student during a study exchange at Osaka University (2023–2024). Using a narrative self-study approach, I carefully examine up to the present moment, the struggles, development, and successes that have reshaped my formerly shaped identity as an English language learner and English education student. Moreover, a collection of reflective writings such as documents, pamphlet notes, tables, and journals were adopted to critically review my identity through a constant comparative method of data analysis, which led to the revelation of multiple stages of my identity formation and then its further reconstruction. The findings reveal that students and teachers’ narrations provide insightful and enlightening clues for each and every engaged member of the learning cycle to learn how to deal with members within their communities, and remind policy-makers and higher-order authorities of the value in recognizing and appreciating each and every one of an individual’s voices.